Efficacy of Lactobacillus vaginal suppositories for the prevention of recurrent cystitis: A phase II clinical trial. (13th July 2021) - Sadahira, Takuya; Wada, Koichiro; Araki, Motoo; Mitsuhata, Ritsuko; Yamamoto, Masumi; Maruyama, Yuki; Iwata, Takehiro; Watanabe, Masami; Watanabe, Toyohiko; Kariyama, Reiko; Nasu, Yasutomo; Ishii, Ayano
Abstract : Objectives: To prospectively assess the efficacy and safety of Lactobacillus vaginal suppositories for the prevention of recurrent cystitis. Methods: In this single‐arm, open‐label, phase II clinical trial, participants used vaginal suppositories containing the GAI 98322 strain of Lactobacillus crispatus for 1 year either every 2 days or three times per week. The primary end‐point was the response rate, as assessed by the number of episodes of recurrent cystitis during the year of administration. The secondary end‐points were the response rate, as assessed by episodes of recurrent cystitis during the 1 year after completion of the administration period; the total number of episodes of recurrent cystitis before, during and after administration; adverse events; and changes in urine bacteria and the vaginal microbiome. Results: A total of 28 women were enrolled, and 21 completed the study. A total of 18 patients achieved an effective response (86%) during administration. The suppressive effects of Lactobacillus vaginal suppositories on episodes of cystitis continued up to 1 year after the last suppository was administered. There was a significant reduction in the mean number of episodes of cystitis, both during and after administration of Lactobacillus vaginal suppositories. No treatment‐related adverse events were observed. Amplicon sequencing analysis of the vaginal microbiome showed that Lactobacillus species colonized the vagina during the periods when episodes of cystitis were absent. Conclusions: Vaginal suppositories containing the GAI 98322 strain of Lactobacillus crispatus effectively prevent episodes of recurrent cystitis, both during administration and for at least 1 year after administration.